EUROPEAN SECTION OF ONCOLOGICAL UROLOGY (ESOU): NEW DATA IN 2017 - S. A. Reva (Вестник урологии)
Summary. The past year has been saturated with information from new research, many of which have already been introduced into the standards. Of course, in a short message it is impossible to cover all the significant works of the year, but at the ESOU congress summarized all the trends that are relevant for actual and promising for the future in the diagnosis and treatment of major oncological diseases.